2014
DOI: 10.4314/ahs.v13i4.27
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and their diagnoses: Bapedi experience

Abstract: The current study concludes that Bapedi traditional healers play an important role in the treatment STIs in the Limpopo Province. Of concern is their diagnosis which is based primarily on the presentation of symptoms and behavioural traits, which are not always accurate indicators. Thus, to make their contribution to the treatment and management of STIs beneficial, they have to receive elementary training in diagnostic methods particularly for HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…South African authors have found that while traditional healers play a key role in the diagnosis and management of sexually transmitted infections including HI/AIDS, they have serious shortcomings especially poor diagnosis. 2 Testing for HIV remains a very important strategy for HIV prevention in South Africa especially for young people. Over 50% of the youth reported that they had had an HIV test with females more likely to test than males.…”
mentioning
confidence: 99%
“…South African authors have found that while traditional healers play a key role in the diagnosis and management of sexually transmitted infections including HI/AIDS, they have serious shortcomings especially poor diagnosis. 2 Testing for HIV remains a very important strategy for HIV prevention in South Africa especially for young people. Over 50% of the youth reported that they had had an HIV test with females more likely to test than males.…”
mentioning
confidence: 99%
“…South African traditional healers see far fewer patients than their biomedical counterparts, offering in-depth treatment that includes counselling for both individual patients and their families [ 46 ]. South African traditional healers, like their Native American counterparts, also frequently travel significant distances to treat patients in their own homes [ 52 ]. Traditional healing is therefore a highly individualised and interactive experience for patients, in which healers are facilitators.…”
Section: The Advantages Of Traditional Healing For Patientsmentioning
confidence: 99%
“…It is also noted that different strains of N. gonorrhoea are susceptible to several plant extracts [15][16][17], and sensitive to pure isolate compounds [18,19]. Gonorrhoea [20] and candidiasis [21] infections are the most common STIs recognised by traditional health practitioners (THPs). Many healthcare seekers in lower socio-economic settings depend on invasive alien plants administered by THPs to treat gonorrhoea and candidiasis [22].…”
Section: Introductionmentioning
confidence: 99%